(untitled) (Papeles, 2025)
Introduction: We live in a violent society, and this has also affected our schools. Therefore, schools need to take action to prevent conflict and improve school coexistence; hence it is necessary to deal with education in values. Methodology: The aim of this article is to know the state of the art in the topic of education in values in primary school, as well as the importance teachers attach to this concept. A documental revision of 609 scientific articles published in open source journals from January 2019 to June 2023 has been carried out. The main databases searched were Dialnet, Education Source, Scopus and ERIC, following the guidelines of Prisma 2020. Results and Discussion: Findings show that these articles are mainly qualitative, and the samples include teachers, parents, non-teaching staff, textbooks, children’s books, and document reviews. Regarding the topic of education in values, the articles highlight the importance of teaching strategies, the family, learning resources, and the need for teacher training regarding knowledge. Conclusions: It can be noted that this systematic revision suggests that games and collaborative work are the most used strategies, and the main learning resources are textbooks and children’s stories. Finally, it can be suggested that families are not fulfilling their roles in values formation therefore, primary school teachers require further professional skills to be able to educate in values.